Cross-species transcriptome-wide meta-analysis of anterior cruciate ligament rupture - Livia Beccacece; Stefano Pallotti; Yiyun Li; Jie Huang; Leonardo Pasotti; Valerio Napolioni (BMC Genomics)
Abstract Background The Anterior Cruciate Ligament (ACL) plays a critical role in maintaining the musculoskeletal stability of the knee. Its injury has been linked to an increased risk of developing osteoarthritis. This study aims to identify cross-species responses to ACL rupture providing insights on its molecular basis. We analyzed five publicly available transcriptomic datasets from Homo sapiens, Mus musculus, Canis lupus familiaris, and Oryctolagus cuniculus. Differential gene expression analysis was performed for each dataset, producing a genome-wide transcriptional signature of fold-change significance for individual genes. Stouffer’s method was used to integrate the results, identifying genes significantly deregulated across all species. Additionally, gene-set enrichment analysis revealed pathways that were consistently upregulated or downregulated. Results A positive correlation in expression was observed between human and the other three species (r2 = 0.177–0.305, p-value ≤ 2.7 × 10− 113), identifying 210 genes as the most consistently up- and down-regulated in response to ACL rupture (p-adjusted ≤ 1.27 × 10− 23). These genes are primarily involved in cellular mitosis, collagen pathways, and cartilage development. Furthermore, 60 pathways were found to be significantly up- or down-regulated across all species (p-adjusted ≤ 4.57 × 10− 4). Among these, the upregulation of inhibition of bone mineralization (p-adjusted ≤ 2.99 × 10− 6) aligns with previous findings on the reduction of subchondral bone mineral density following ACL rupture. Conclusions This study highlights that distinct species exhibit common molecular responses to ACL rupture, underscoring the value of mice, dogs, and rabbits as potential translational model organisms for ACL rupture research. Furthermore, the identified genes and pathways highlight the molecular mechanisms underlying ACL rupture.